2015
DOI: 10.1061/(asce)ee.1943-7870.0000937
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Properties and Test Conditions on Sorption and Desorption of Testosterone

Abstract: In this study, batch sorption and desorption experiments were conducted for testosterone using four agricultural soils and five clay minerals. Significant differences in sorption behavior were observed between abiotic and biotic systems. The Freundlich sorption coefficient K f ðμg=gÞ=ðμg=mLÞ n ranged from 8.53 to 74.46 for soils and from 35.28 to 1,243 for clays. The maximum sorption capacity (μg=g) of soils ranged from 25.25 to 440.61 for soils and from 168.46 to 499.84 for clays. Correlation of the sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Testosterone was selected as the representative hormone because 1) it is a prototype for other synthetic androgenic hormones (Kanayama and Pope 2012); 2) little is known about the F/T of androgenic hormones (Casey et al, 2004); and 3) it was used previously (Qi et al, 2014;Qi and Zhang 2015a;Ma et al, 2015). In the present study, sorption tests were conducted with testosterone at environmentally relevant low concentration levels (20−150 ng/L) (Finlay-Moore et al, 2000).…”
Section: Selected Hormones and Soilsmentioning
confidence: 99%
“…Testosterone was selected as the representative hormone because 1) it is a prototype for other synthetic androgenic hormones (Kanayama and Pope 2012); 2) little is known about the F/T of androgenic hormones (Casey et al, 2004); and 3) it was used previously (Qi et al, 2014;Qi and Zhang 2015a;Ma et al, 2015). In the present study, sorption tests were conducted with testosterone at environmentally relevant low concentration levels (20−150 ng/L) (Finlay-Moore et al, 2000).…”
Section: Selected Hormones and Soilsmentioning
confidence: 99%
“…On the contrary, sorption is inversely proportional to desorption. Ma et al [19] studied the desorption capacity of testosterone in the same soil and found less than 10% desorption after first cycle of analysis which indicated low desorption of testosterone in the soil-water systems especially if it was sorbed on top soil or on a soil with high clay content. A greater OM content caused stronger binding of testosterone with soil and resulted less desorption.…”
Section: Frequency Of Detection In Runoff Samplesmentioning
confidence: 99%
“…Both natural and synthetic hormones and their metabolites have been detected in manure, soil and wastewater of cattle feedlots [13][14][15][16]. Studies evaluating the persistence of specific hormones in soils observed that most steroid hormones and their metabolites exhibit relatively strong adsorption-desorption characteristics with low aqueous solubility [17][18][19]. Soil microbiology and surrounding physio-chemical characteristics are major factors controlling transformation among the steroid hormones and their metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2015) suggested that clay content, soil organic matter, temperature, ionic strength, water/soil ratio, and soil depth affected the sorption and desorption of testosterone in soil. The Freundlich sorption coefficients K f of the four agricultural soils and the five clay minerals evaluated were 8.53–74.46 and 35.28–1,243 (μg/g)/(μg/mL) n , respectively.…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…Ma et al (2015) investigated the occurrence of 20 antibiotics during the groundwater recharge process across China. Fifteen locations employing reclaimed water located in different humid, semi-humid and semi-arid regions were identified, and samples of both reclaimed and ground water were analyzed.…”
Section: Pharmacuetical Contaminantsmentioning
confidence: 99%